Assessment of the validity and reliability of an urban household health expenditure (HHE) questionnaire in Kuala Lumpur, Malaysia - Murallitharan Munisamy; Tharini Thanapalan; Pattaraporn Piwong; Alessio Panza; Sathirakorn Pongpanich (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Out-of-pocket (OOP) payments continue to be a major method of financing healthcare in many low- and middle-income countries including Malaysia. Although macro-level data show that this is a substantial percentage of national health expenditure, at the grassroots level, the amount spent on health by households remains unknown in Malaysia. The purpose of this paper is to assess the validity and reliability of an adapted-for-purpose questionnaire designed to capture urban household health expenditures (HHEs) among Malaysian households. Design/methodology/approach - This two-part study assessed content validity of the questionnaire using three experts and the reliability of the questionnaire through a test-retest study among 50 OOP-paying patients followed up at one private primary care clinic in Kuala Lumpur. This study was approved by the Malaysian Research Ethics Committee (NMRR-16-172-29311-IIR). Findings - The validity of the 83-item questionnaire was high, with an item content validity index of 1.00 and a scale content validity index average score of 1.0 agreed to among the evaluating experts. In the test-retest reliability study, the majority of the categorical questionnaire items had perfect agreement values (k=0.81-1.00). Continuous questionnaire items were also found to be highly reliable with no significant differences between the test-retest segments and high correlation coefficient values (intra-class correlation coefficient>0.7). Originality/value - The HHE questionnaire had excellent content validity and very high test-retest reliability. The results of this study suggest that this questionnaire could be used in Malaysian studies to determine actual urban HHE which is a first step toward developing universal health coverage for all.